2022
DOI: 10.21037/atm-21-5400
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of bilateral breast cancer: a single-center cohort study based on Chinese data

Abstract: Background The incidence of bilateral breast cancer (BBC) is low, accounting for 5% of patients with breast cancer. This study aimed to investigate the clinicopathological features and prognosis of synchronous bilateral breast cancer (SBBC) and metachronous bilateral breast cancer (MBBC) in the Chinese population. Methods Patients with BBC, including SBBC and MBBC, were selected from 6,162 breast cancer patients who underwent surgery at the Chinese People’s Liberation A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To avoid potential dependency and information leakage between the 2 tumors and N statuses, we excluded patients with bilateral tumors. The exclusion limits the target group to a minor extent, as bilateral cancers are generally diagnosed in <5% of patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid potential dependency and information leakage between the 2 tumors and N statuses, we excluded patients with bilateral tumors. The exclusion limits the target group to a minor extent, as bilateral cancers are generally diagnosed in <5% of patients [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MBBC patients with contralateral cancer diagnosed more than five years apart, had a similar prognosis as unilateral breast cancer [4]. In another study [6], patients with MBBC were found to have a worse disease-free survival compared to patients with unilateral breast cancer. However, the overall survival was similar for both groups of patients.…”
Section: Introductionmentioning
confidence: 93%
“…We excluded bilateral patients not to risk dependency and information leakage between the two tumors and/or nodal statuses. The exclusion limits the target group to a minor extent, as bilateral cancers are generally diagnosed in less than 5% of patients [46].…”
Section: Strengths and Limitationsmentioning
confidence: 99%